A study on the relationship between employee benefit and employee work productivity at Majlls Daerah Raub (MDR) / Aqilah Hashim - Hashim, Aqilah (Faculty of Business Management, 2018)
Employee benefit or welfare can be characterized as a corporate attitude or duty reflected in the imparted watch over a worker at all measures, supporting their work and the earth in which it is performed. A large portion of the companying as a rule see the employee benefit as important for their employee however they do not know about the most imperative one. The goal of studying about employee benefits is to know what are the most preferred benefits and which benefit give more impact on employee work productivity. The study has identified the type of employee's benefits that employees need the most and to determine the relationship between employee's benefits and employees' productivity in a Majlis Daerah Raub (MDR), Pahang. For this study, the sampling frame that is used was based on the list of employees' in MDR, Pahang. The population of the study consists of employees from MDR and the total numbers of the population are approximately 159 employees. Besides that, this study used the simple random sampling as the sampling technique and there were 113 sample sizes that randomly based on 159 totals of employees. The researchers also had been used in the questionnaire to collect the data. Hence, the questionnaires were including six sections and it was using the five-point Likert Scale to identify the respondents' rate. Based on the findings, the type of employees' benefit that employee needs the most was child care service and the overall results of the relationship between employee benefits and employee work productivity can be donated that there was a strong relationship between dependent variable and independent variables. For recommendation, the researcher wants the employer to be aware of the employees benefit provided to the staff and the employer should provide the benefit that employee needs. In addition, the employees need to be aware of the importance of the benefits that were provided for them. Lastly, the researcher wants to increase the sample size of the respondents to answer the questionnaires, study on other variables of employee benefit and to improve the awareness among the staff on the employee benefit.